2007
DOI: 10.1097/mao.0b013e31815882a6
|View full text |Cite
|
Sign up to set email alerts
|

Probabilities of Ossicular Discontinuity in Chronic Suppurative Otitis Media Using Pure-Tone Audiometry

Abstract: Narrow ABG at lower frequencies suggested absence of OD. Wide ABG at higher frequencies suggested presence of OD. Simple tympanoplasty can be done to patients with a small chance of OD as assessed by pure-tone audiometry, whereas a mandatory exploration of the ossicular chain with possible reconstruction was suggested on subjects with a high chance of OD. The presence of cholesteatoma warrants ossicular chain exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 7 publications
1
26
2
Order By: Relevance
“…Regarding hearing function, ABG in patients affected by chronic otitis media is usually related to the ossicular chain condition; in particular, a narrow ABG would suggest ossicle integrity, whereas a wide ABG would predict ossicular resorption [ 7 ]. This was not fully confirmed by our study.…”
Section: Discussioncontrasting
confidence: 73%
“…Regarding hearing function, ABG in patients affected by chronic otitis media is usually related to the ossicular chain condition; in particular, a narrow ABG would suggest ossicle integrity, whereas a wide ABG would predict ossicular resorption [ 7 ]. This was not fully confirmed by our study.…”
Section: Discussioncontrasting
confidence: 73%
“…This was supported by Ryner Jose C stating that although mastoidectomy may be done on simple TM perforations there was no clear advantage for its routine practice in CSOM in absence of active infection or disease. 13 In contrast to our study, a study conducted by Holmquist et al suggested that mastoidectomy improves the chance of successful tympanoplasty for patients with noncholesteatomatous chronic otitis media. They maintained that creation of an aerated mastoid enhances success in patients with poor tubal function or a small mastoid air cell system.…”
Section: Discussioncontrasting
confidence: 53%
“…16 Carillo et al studied Pure Tone Audiometric Thresholds in patients who underwent tympanomastoidectomy and found that a wide Air-Bone Gap at higher frequencies was more suggestive of incus necrosis. 17 In contrast to this, according to Jeng et al, Air-Bone Gap is not a good predictor of ossicular necrosis as granulations could bridge the defect between eroded ossicles thus reducing the Air-Bone Gap. 4 Presence of Middle ear granulations was found to be statistically significant predictor for ossicular necrosis in Ebenezer J et al and Jayakumar CL et al studies.…”
Section: Discussionmentioning
confidence: 93%